Anti-retroviral drugs: current state and development in the next decade - Xingquan Zhang (Acta Pharmaceutica Sinica B, 2018)
The pace of discovery of new antiretroviral (ARV) drugs has slowed, although the efficacy and safety of once-daily fixed dose combinations have been extensively investigated. Several traditional ARV drugs remain in phase III clinical trials. This review summarizes current information on ARV drugs in phase III clinical trials and focuses on the development of ARV drugs in the next decade. KEY WORDS: Antiretroviral drugs, Long-acting formulations, Attachment inhibitors, Maturation inhibitors, Nanomedicine